Antimicrobial and Antioxidant Activities of Some Xylariaceous Fungi - Panjaitan, Desimaria; Noraini; Norwahyunie; Fastanti, Fandri Sofiana; Naibaho, Frans Grovy (Biotropika: Journal of Tropical Biology, 2025)
The Xylariaceae family comprises cosmopolitan ascomycetous fungi that predominantly live as saprobes, contributing ecologically and forming interactions with various organisms. Due to their cultivability under laboratory conditions and potential to produce bioactive metabolites, members of Xylariaceae are increasingly explored for bioprospecting. This study aimed to evaluate the antimicrobial and antioxidant activities of mycelial extracts from Xylariaceae isolates collected from Central Kalimantan, Indonesia, as an initial step in exploring their bioprospective traits. Fungal specimens obtained from forest exploration were cultured in vitro to obtain axenic cultures. Liquid-state fermentation was performed to induce metabolite secretion, and the biomass was extracted (macerated) using ethyl acetate (EtOAc) and methanol (MeOH). The antimicrobial activity was tested against Bacillus cereus, Staphylococcus aureus, and Candida albicans using the disk diffusion method. Antioxidant capacity was assessed via the DPPH radical scavenging assay and expressed as IC50 values. Morphological examination of six isolates (DP61–DP66) revealed characteristic features of Xylariaceae, such as upright stromata, clavate dark structures, and smooth to punctate surfaces, while their mycelia appeared white and unpigmented. Ethyl acetate extracts generally exhibited broader antibacterial effects than methanolic extracts. The EtOAc-DP62 extract exhibited strong antibacterial activity, with inhibition zones of 13.3 mm and 13.2 mm against B. cereus and S. aureus, respectively. MeOH-DP66 demonstrated the strongest antifungal activity, with an inhibition zone of 21.7 mm. DP62 also exhibited potent antioxidant activity (IC50 = 3.44 µg/mL), surpassing ascorbic acid (IC50 = 28.32 µg/mL). Molecular identification based on ITS-rDNA sequences revealed DP62 as Nectriopsis epimycota (Bionectriaceae) and DP66 as Xylaria plebeja (Xylariaceae). Interestingly, DP62 may represent an endohyphal fungus initially associated with a xylariaceous fruiting body. These findings highlight the bioprospective value of these fungal isolates as promising antimicrobial and antioxidant-producing agents.